PENGGUNAAN CLOUD COMPUTING DALAM PERANCANGAN APLIKASI MOBILE BERKONSEP GAMIFIKASI BERKEBUN - Korbafo, Adrianus Ragil Indrajaya; Nababan, Darsono; Risald, Risald (Universitas Methodist Indonesia, 2023)
Climate change causes an increase in global temperature, which results in rising sea levels and threatens many cities in the future, including Jakarta. Carbon emissions are the primary cause of climate change, which is difficult to reduce. Forests can act as a natural filter for carbon emissions, but deforestation still occurs for various reasons. The author and their team propose a solution by creating an application called